Answer:
The answer is -11
Step-by-step explanation:
-11 + 5 = -6
Mark as brainliest ^-^
Answer:
192
Step-by-step explanation:
Multiply 3/4 by 256
5^2 = 25 so i would say its 4.8 Answer
Answer: Choice A
y = -3(x+2)^2 + 10
=================================================
Work Shown:
y = -3x^2-12x-2 is in the form y = ax^2+bx+c with
a = -3
b = -12
c = -2
The x coordinate of the vertex is
h = -b/(2a)
h = -(-12)/(2*(-3))
h = 12/(-6)
h = -2
We'll plug this into the original equation to find the corresponding y coordinate of the vertex.
y = -3x^2-12x-2
y = -3(-2)^2-12(-2)-2
y = 10
So k = 10 is the y coordinate of the vertex.
Overall, the vertex is (h,k) = (-2,10)
Meaning that we go from this general vertex form
y = a(x-h)^2 + k
to this
y = -3(x - (-2))^2 + 10
y = -3(x+2)^2 + 10
Answer: please help me with this, I will do whatever you want but please help me please!
Step-by-step explanation: